Correlation between human chronological age and dentin volume of maxillary canine - Pandji, Alisha Zuchraini; Lita, Yurika Ambar; Yohana, Winny (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: One of the identification methods in forensic odontology is to estimate age through tooth characteristics. With age, odontoblast cells that line the pulp cavity will continue the process of secondary dentin deposition at a lower rate. Generally, maxillary canines are teeth that can survive in the oral cavity until old age and are less likely to wear out. This study aimed to determine the correlation between human chronological age and the dentin volume of the maxillary canines using CBCT radiographs. Methods: An analytic study of the Pearson correlation test was conducted on 114 samples of CBCT radiographs of the maxillary canines from the Radiology Unit of the Rumah Sakit Gigi dan Mulut, Faculty of Dentistry, Universitas Padjadjaran. The inclusion criteria for this study were canines with closed apex, no caries, no attrition, no restorations, no orthodontic treatment, and generally good health. Maxillary canine dentin volume was measured using the application ITK-SNAP version 3.8.0. The results of dentin volume were analyzed using the Pearson correlation test using SPSS IBM Statistics 25. Results: Pearson correlation analysis showed the correlation coefficient value (r= 0.270 and (r = 0.427) for the male and female samples, respectively. Conclusion: The correlation between chronological age and maxillary canine dentin volume in this study was not strong enough to be used as a single parameter in the age estimation method. Future research is expected to expand the sample size with a homogenous age distribution to obtain more consistent and accurate results.Keywords: age estimation; dentin volume; maxillary canines; ITK-SNAP; CBCT.